МАСС-МЕДИА И ФИЛОСОФИЯ: ФИЛОСОФСКО- АНТРОПОЛОГИЧЕСКИЙ ДИСКУРС - Мазоренко, М. О. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science")
В статье обобщены основные направления взаимодействия масс-медиа и философии и обоснованы два важнейших тезиса: во-первых, масс-медийное пространство является не только предметом философской рефлексии, а и полем формирования философских дискурсов относительно не масс-медийных стратов общественной и культурной жизни; во-вторых, эти дискурсы имеют ясно выраженный философско-антропологический характер. М.О. Мазоренко МАС-МЕДІА І ФІЛОСОФІЯ: ФІЛОСОФСЬКО-АНТРОПОЛОГІЧНИЙ ДИСКУРС У статті узагальнені основні напрями взаємодії мас-медіа та філософії і обґрунтовані дві важливих тези: по-перше, мас-медійний простір є не тільки предметом філософської рефлексії, але й полем формування філософських дискурсів відносно не мас-медійних стандартів суспільного і культурного життя; по-друге, ці дискурси мають яскраво виражений філософсько- антропологічний характер. Ключові слова: медіа, медіареальность, філософія, медіафілософія, дискурс, комунікація. M. Mazorenko MEDIA AND PHILOSOPHY: PHILOSOPHICAL-ANTHROPOLOGICAL DISCOURSE The article generalizes the main directions of the interaction between mass-media and philosophy and two clue teheses have been supplemented: firstly, mass-media space is not only subject for philosophical reflection but place where philosophical discourses have been formed towards not massmedial stratas of the social and cultural life. Secondly, these discourses have definitely philosophical and anthropological character. Key words: media, a media reality, philosophy, media philosophy, a discourse, communications.